2020
DOI: 10.1016/j.psj.2019.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Standardized ileal digestible amino acid and metabolizable energy content of wheat from different origins and the effect of exogenous xylanase on their determination in broilers

Abstract: This study was conducted to determine the standardized ileal digestible amino acids ( SID AA ) and nitrogen-corrected apparent metabolizable energy ( AMEn ) contents of 6 wheats from different origins in China and incidentally to investigate the effects of exogenous xylanase addition on SID AA and AMEn determination in broiler chicks. A total of 480 chicks were divided into 48 cages of 10 birds each balanced for body weight and fed 8 types of diets in a completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
4
14
2
Order By: Relevance
“…Nitrogen-free diets (NFD) are traditionally used in monogastric animals to calculate SID, where the IEAAs losses are determined by measuring AA excretion in the ileal digesta 5 . Corn starch and dextrose are the main components of the NFD (approximately 80% of NFD), but the ratio of dextrose to corn starch (D/CS) varies in literature (0.21–3.79) 6 9 , which may, in turn, affect the flow of IEAAs. Kong et al 10 identified that total IEAAs were significantly higher when dextrose was used as a sole source of energy in NFD than corn starch (17,544 vs. 12,779 mg/kg of dry matter intake).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-free diets (NFD) are traditionally used in monogastric animals to calculate SID, where the IEAAs losses are determined by measuring AA excretion in the ileal digesta 5 . Corn starch and dextrose are the main components of the NFD (approximately 80% of NFD), but the ratio of dextrose to corn starch (D/CS) varies in literature (0.21–3.79) 6 9 , which may, in turn, affect the flow of IEAAs. Kong et al 10 identified that total IEAAs were significantly higher when dextrose was used as a sole source of energy in NFD than corn starch (17,544 vs. 12,779 mg/kg of dry matter intake).…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of ME, the ad libitum feeding method is becoming increasingly popular compared to the labor-intensive and time-consuming method of force-feeding. However, there is a lack of consensus on fasting duration ( Lu et al., 2020 ; Yang et al., 2020 ), which necessitates investigating a new fasting procedure in ME assays.…”
Section: Introductionmentioning
confidence: 99%
“…In monogastric animals fed on nitrogen-free diets (NFD), the IEAAs losses have traditionally been determined by measuring AA excretion in the ileal digesta 4 . Corn starch and dextrose or sucrose are the main components of the NFD (approximately 80% of NFD) [5][6][7][8] . Interestingly, corn starch to dextrose or sucrose ratio varies (0.31 to 9.52) in literature [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Corn starch and dextrose or sucrose are the main components of the NFD (approximately 80% of NFD) [5][6][7][8] . Interestingly, corn starch to dextrose or sucrose ratio varies (0.31 to 9.52) in literature [5][6][7][8] . This clearly indicates that there is no uni ed standard for the proportion of starch and dextrose in the NFD formula.…”
Section: Introductionmentioning
confidence: 99%